Temperature and doping dependence of normal state spectral properties in a two-orbital model for ferropnictides - Querales Flores, Jose Daniel (2016)
Using a second-order perturbative Green's functions approach we determined the normal state spectral function A(k→,ω) employing a minimal model for ferropnictides. Used before to study magnetic fluctuations and superconducting properties, it includes the two effective bands related to Fe-3d orbitals proposed by S. Raghu et al. [Phys. Rev. B 77 (2008) 220503(R)], and local intra- and inter-orbital correlations for the effective orbitals. Here, we focus on the normal state electronic properties, in particular the temperature and doping dependence of the total density of states, A(ω), and of A(k→,ω) in different Brillouin zone regions, comparing them with existing angle resolved photoemission spectroscopy (ARPES) and theoretical results. We obtain an asymmetric effect of electron and hole doping, quantitative agreement with the experimental chemical potential shifts, as well as spectral weight redistributions near the Fermi level with temperature consistent with the available experiments. In addition, we predict a non-trivial dependence of A(ω) with temperature, exhibiting clear renormalization effects by correlations. Interestingly, investigating the origin of this predicted behavior by analyzing the evolution with temperature of the k-dependent self-energy obtained in our approach, we could identify a number of Brillouin zone points, not probed by ARPES yet, where the largest non-trivial effects of temperature on the renormalization are predicted for the parent compounds.